Educating for emancipation: an analysis of the concept of awareness and educational practice in Paulo Freire's theory - Nascimento, Isabela Ribeiro Villares; Lima, Cláudia Araújo de; Quadros Rückert, Fabiano (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: This article aims to discuss the concept of awareness and educational practice in the evolution of thinking about education aimed at the popular class, in the works of Paulo Freire, with theoretical contributions for reflections on Brazilian political, economic and social factors, in the decades of 1950 – 1960. Originality/contribution: The original article is anchored in a discussion by axes, where a historical period marked by intense transformations in the life of the popular classes is debated, when government investments in industry denoted an increase in rural-urban migration and the formation of a mass of illiterate workers in Brazilian cities. Method:The research method listed for this study was a survey, systematization and bibliographic analysis, from descriptors close to the theme and determined period, using the tools of content analysis for the elaboration of the article. Information strategy/data collection The collection of information was based on bibliographic surveys in Brazilian and foreign collections that dealt with the discussion about awareness and educational practices in the specific period. Conclusions:As conclusions, it is observed that the changes that took place over the decades acted directly in the structuring of Paulo Freire's theory on education. As a criticism of the education given to workers, the concept of awareness and educational practice, were consolidated as the basis of Freirean pedagogy and are progressively developed and complexified in the author's works. The enunciated concepts offer subsidies to the current analyzes on the social function of the school and the human formation.